NanoSQUIDs from YBa2Cu3O7/SrTiO3 superlattices with bicrystal grain boundary Josephson junctions. Issue 38 (30th September 2020) - Lin, Jianxin; Linek, Julian; Kleiner, Reinhold; Koelle, Dieter
Abstract : We report on the fabrication and characterization of nanopatterned dc SQUIDs with grain boundary Josephson junctions based on heteroepitaxially grown YBa2 Cu3 O7 /SiTrO3 superlattices. Abstract : We report on the fabrication and characterization of nanopatterned dc SQUIDs with grain boundary Josephson junctions based on heteroepitaxially grown YBa2 Cu3 O7 (YBCO)/SiTrO3 (STO) superlattices on STO bicrystal substrates. Nanopatterning is performed by Ga focused-ion-beam milling. The electric transport properties and thermal white flux noise of superlattice nanoSQUIDs are comparable to single layer YBCO devices on STO bicrystals. However, we find that the superlattice nanoSQUIDs have more than an order of magnitude smaller low-frequency excess flux noise, with root-mean-square spectral density at 1 Hz ( Φ 0 is the magnetic flux quantum). We attribute this improvement to an improved microstructure at the grain boundaries forming the Josephson junctions in our YBCO nanoSQUDs.